Influence of early food introduction on the development of childhood obesity: a literature review (Research, Society and Development, 2020)
A better understanding of the predictors of childhood obesity is essential to effectively target public health interventions. The objective of this integrative review was to verify whether the introduction of early complementary feeding can related to the development of childhood obesity. For the selection of studies, publications indexed in the following databases were searched: (MEDLINE / Pubmed, ScienceDirect, LILACS and SCIELO). For the choice of writings in the databases, the following descriptors were used: "Diet", "Pediatric obesity" and "Breast feeding". Studies of preterm children and children with conditions that can influence growth, articles who had only abstract available and experimental animal studies were excluded. 16 studies met the inclusion criteria for the integrative review. No clear association was found between the age of initiation of solid feed and obesity. It is presumed that genetic and environmental factors have a greater impact on childhood obesity. This leads to the conclusion that all nutritional education work with a family approach to obesity prevention will certainly be more effective than working to change a single factor, wich is the timing of the introduction of solid feed.